Cannabis effects on lipoproteins. Issue 2 (April 2019) - Lazarte, Julieta; Hegele, Robert A.
Abstract : Purpose of review: The endocannabinoid system affects several physiological functions. A family of endocannabinoid receptors is susceptible to cannabis constituents. Cannabis is widely used in our society and following its recent legalization in Canada, we focus on how exposure to cannabis and pharmacologic cannabinoid receptor type 1 (CB1) inhibition affect lipoprotein levels. Recent findings: Several groups have reported that exposure to cannabis does not increase weight despite the marked increase in caloric intake. In observational studies, the effect of smoked cannabis exposure on plasma lipids is variable. Some studies in specific patient populations with longer exposure to cannabis seemed to identify slightly more favorable lipoprotein profiles in the exposed group. Several larger controlled clinical trials using orally administered rimonabant, a CB1 receptor antagonist, have consistently shown relative improvements in weight and plasma levels of triglyceride and high-density lipoprotein cholesterol among patients receiving the treatment. Summary: The widely variable findings on the relationship of cannabis in various forms with plasma lipids preclude any definitive conclusions. Cannabis has complex effects on the cardiovascular system and its effects on lipid profile must be considered in this overall context. Further properly controlled research is required to better understand this topic.